Teratogenicity of Carbamazepine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The teratogenic risk after first trimester exposure to carbamazepine was determined from 210 pregnancies followed prospectively at the Israeli Teratogen Information Service, and Laboratory of Teratology, Hebrew University, Hadassah Medical School, and Ministry of Health, Jerusalem, Israel.